Automation of the process of generation of the students insurance, applying RFID and GPRS technologies (2013)
This article presents the description of the design and implementation of a system which allows the fulfilment of a consultation service on various parameters to a web server using a GSM modem, exchanging information systems over the Internet (ISS) and radio-frequency identification (RFID). The application validates for its use in automation of the process of generation of the student insurance, and hardware and software, developed by the Research Group in Robotics and Industrial Automation GIRAof UPTC, are used as a platform.